Towards Paul Tillich’s theology of culture: a problem of demarcation of “sacred” and “secular” - Eduard SABLON LEIVA (Богословські роздуми: Східноєвропейський журнал богословʼя)
This article focuses on the dichotomy found within categorical pairs such as religion and culture, сhurch and society, and theology and philosophy – a problematical dichotomy in the horizon of Paul Tillich’s theology of culture. In particular, Tillich’s philosophical-theological approach to solving this problem is considered, namely, his theology of culture’s hermeneuticalapologetical key: the “method of correlation.” Tillich’s intrinsic aims, along with certain ideas he borrowed from Western thinkers, and how these inform his system, are the object of review and analysis throughout the article. The article indicates, finally, the system’s main benefits and its contributions to interdisciplinary dialogue (between theology and the sciences, especially philosophy) and the dialogue between Church and Culture.